2000
DOI: 10.1097/00001813-200001000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer drug-induced apoptosis in human monocytic leukemic cell line U937 requires activation of endonuclease(s)

Abstract: Anticancer agents effect tumor cell killing both in vivo and in vitro through the induction of apoptosis. Endonuclease-mediated internucleosomal DNA fragmentation, the most widely used biochemical marker of apoptosis, has been shown to play a central role in apoptosis in many experimental systems. In the present investigation, we report that activation of endonuclease(s) leading to oligonucleosomal DNA fragmentation is common and an essential event in apoptosis, induced by different anticancer drugs, adriamyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…The role of endonucleases in the apoptosis of cancer cell death was demonstrated in several studies, however the major endonuclease responsible for breast epithelium and breast cancer cell death was not determined [9,10]. In the current study, we presented evidence that EndoG is the major endonuclease in breast epithelium and breast cancer cells.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The role of endonucleases in the apoptosis of cancer cell death was demonstrated in several studies, however the major endonuclease responsible for breast epithelium and breast cancer cell death was not determined [9,10]. In the current study, we presented evidence that EndoG is the major endonuclease in breast epithelium and breast cancer cells.…”
Section: Discussionmentioning
confidence: 47%
“…Anticancer drugs induce apoptosis in cancer cells through endonuclease-mediated DNA fragmentation [9,10], while the inhibition of endonucleases has a protective effect on cancer cell death [10]. Cell death endonucleases include deoxyribonuclease I (DNase I) [11], deoxyribonuclease II (DNase II) [12], endonuclease G (EndoG) [13], caspase-activated DNase (CAD) [14], and DNase gamma [15].…”
Section: Introductionmentioning
confidence: 99%
“…Because it has recently been reported that cancer chemotherapeutics exert part of their pharmacological effect by triggering apoptotic cell death (Shrivastava et al, 2000), apoptosis-inducing compounds in tumor cells have become useful as lead compounds for the development of anticancer drugs. In the present study, IC101 in the range of 1 nM to 1 M induced cell death in a concentration-dependent manner with an EC 50 value of 20 nM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In other cells, EndoG has been recognized as a key endonuclease in the caspase-independent apoptosis (Abbott et al, 2001;Bahi et al, 2006), mitotic catastrophe (Diener et al, ;Wang et al, 2008), and necrosis (Apostolov et al, 2007a;Jiang et al, 2006). Because anticancer drugs induce apoptosis in cancer cells through endonuclease-mediated DNA fragmentation (Ploski & Aplan, 2001;Shrivastava et al, 2000), and the inhibition of endonucleases has a protective effect (Shrivastava et al, 2000), endonuclease should be considered as important mediators of cancer cell death and potential therapeutic targets for www.intechopen.com the anticancer therapy. However, delivery of endonucleases or modulation of endonuclease activity are not currently used for cancer therapy, in particular, for prostate cancer therapy.…”
Section: Cytotoxic Endonucleases In Normal Prostate and Prostate Cancmentioning
confidence: 99%